2017
DOI: 10.1002/pmic.201600455
|View full text |Cite
|
Sign up to set email alerts
|

Targeted label‐free quantification of interleukin‐8 in PMA‐activated U937 cell secretome by nanoLC‐ESI‐MS/MS‐sSRM

Abstract: Monocytes are a part of the innate immune system. Their differentiation into macrophages changes their cellular proteome and secretome. Particularly secretome components such as cytokines are crucial for immune response and inflammation in many diseases. Differentiation of human lymphoma cell line U937 can be triggered by phorbol 12-myristate 13-acetate (PMA). Screening of the cytokine release in U937 upon PMA stimulation by cytometric bead array almost exclusively showed interleukin-8 (IL-8). Next, a label-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The supernatants were collected and stored at −80 °C. The conditioned media (CM) were analyzed by CBA . Cytokine concentrations were analyzed following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatants were collected and stored at −80 °C. The conditioned media (CM) were analyzed by CBA . Cytokine concentrations were analyzed following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The conditioned media (CM) were analyzed by CBA. [15] Cytokine concentrations were analyzed following the manufacturer's instructions. The BD TM CBA Human Inflammatory Cytokine Kit was used for quantitative measurement of the protein levels of the human cytokines IL-8, IL-1β, IL-6, IL-10, TNF, and IL-12p70 in supernatants of cultured cells.…”
Section: Cba For Quantification Of Selected Cytokinesmentioning
confidence: 99%
“…PMA also activates RhoA/ROCK signaling during monocyte to macrophage differentiation resulting in morphological changes and increased cell adherence (Yang et al, 2017). However, there is a wide range of PMA concentrations being used in the reported experiments, and this wide range could affect the macrophage status through mechanisms such as the increased transcription levels of adhesion molecules CD44, CD14, ICAM-1 or the extracellular matrix FN1 in high-dose PMA treatments (Song et al, 2015;Emirbayer et al, 2017). A previous study found that THP-1 macrophages differentiated in high concentrations of PMA rap-idly died following infection whereas those differentiated in low concentrations of PMA survived and were able to control the intracellular Salmonella Typhimurium bacteria similar to primary human macrophages (Starr et al, 2018).…”
Section: Introductionmentioning
confidence: 99%